Testing the Sound Quality of Acoustic Vacuum Tube Amplifier - Stanisław MALECZEK (Archives of Acoustics, 2008)
The study presents analysis of basic electrical parameters and sound quality of two acoustic amplifiers: an acoustic vacuum tube amplifier and a transistor amplifier. Computer-aided measurement methods have been used through the tests. For the measurement of basic electrical parameters, specialized computer stands and a computer psychoacoustic model have been used. Additionally, audio monitoring has been carried out. The paper is an attempt of answering the question: why tube amplifiers, despite worse electric parameters sound much better than transistor amplifiers do.